Financial crises : lessons from the past, preparation for the future - Caprio, Gerard; Hanson, James A.; Litan, Robert E., 1950- (Brookings Institution Press, 2005)
"Analyzes the efficacy of attempts to recover from past crises and their lessons for the future, assesses the current state of international financial markets and examines policy options for reducing systemic vulnerability, and addresses pension system reform"--Provided by publisher.